Compensatory Reserve Index: Performance of A Novel Monitoring Technology to Identify the Bleeding Trauma Patient. Issue 3 (March 2018) - Johnson, Michael C.; Alarhayem, Abdul; Convertino, Victor; Carter, Robert; Chung, Kevin; Stewart, Ronald; Myers, John; Dent, Daniel; Liao, Lilian; Cestero, Ramon; Nicholson, Susannah; Muir, Mark; et al.
ABSTRACT: Introduction: Hemorrhage is one of the most substantial causes of death after traumatic injury. Standard measures, including systolic blood pressure (SBP), are poor surrogate indicators of physiologic compromise until compensatory mechanisms have been overwhelmed. Compensatory Reserve Index (CRI) is a novel monitoring technology with the ability to assess physiologic reserve. We hypothesized CRI would be a better predictor of physiologic compromise secondary to hemorrhage than traditional vital signs. Methods: A prospective observational study of 89 subjects meeting trauma center activation criteria at a single level I trauma center was conducted from October 2015 to February 2016. Data collected included demographics, SBP, heart rate, and requirement for hemorrhage-associated, life-saving intervention (LSI) (i.e., operation or angiography for hemorrhage, local or tourniquet control of external bleeding, and transfusion >2 units PRBC). Receiver-operator characteristic (ROC) curves were formulated and appropriate thresholds were calculated to compare relative value of the metrics for predictive modeling. Results: For predicting hemorrhage-related LSI, CRI demonstrated a sensitivity of 83% and a negative predictive value (NPV) of 91% as compared with SBP with a sensitivity to detect hemorrhage of 26% ( P  < 0.05) and an NPV of 78%. ROC curves generated from admission CRI and SBP measures demonstrated values of 0.83 and 0.62, respectively. CRI identified significant hemorrhage requiring potentially life-saving therapy more reliably than SBP ( P  < 0.05). Conclusion: The CRI device demonstrated superior capacity over systolic blood pressure in predicting the need for posttraumatic hemorrhage intervention in the acute resuscitation phase after injury.